Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Sex differences in the association between skeletal muscle energetics and perceived physical fatigability: the Study of Muscle, Mobility and Aging (SOMMA) - Emma L. Gay; Paul M. Coen; Stephanie Harrison; Reagan E. Garcia; Yujia Qiao; Bret H. Goodpaster; Daniel E. Forman; Frederico G. S. Toledo; Giovanna Distefano; Philip A. Kramer; Sofhia V. Ramos; Anthony J. A. Molina; et al. (GeroScience, 2024)

P01-33 Toxicity induced by cigarette smoke and electronic cigarette aerosols - K. Partsinevelos; R. Emma; A. Distefano; G. Carota; S. Rust; R. Pulvirenti; D. Campagna; R. Polosa; M. Caruso; G. Li Volti (Toxicology Letters, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Genetic structure analysis and selection of a core collection for carob tree germplasm conservation and management - M. Di Guardo; F. Scollo; A. Ninot; M. Rovira; J. F. Hermoso; G. Distefano; S. La Malfa; I. Batlle (Tree Genetics & Genomes, 2019)

Receptor-mediated toxicity of human amylin fragment aggregated by short- and long-term incubations with copper ions - Giuseppe Caruso; Donatella A. Distefano; Paolo Parlascino; Claudia G. Fresta; Giuseppe Lazzarino; Susan M. Lunte; Vincenzo G. Nicoletti (Molecular and Cellular Biochemistry, 2017)

Effects of historical lead–zinc mining on riffle-dwelling benthic fish and crayfish in the Big River of southeastern Missouri, USA - A. L. Allert; R. J. DiStefano; J. F. Fairchild; C. J. Schmitt; M. J. McKee; J. A. Girondo; W. G. Brumbaugh; T. W. May (Ecotoxicology, 2013)

Effects of Mining-Derived Metals on Riffle-Dwelling Crayfish in Southwestern Missouri and Southeastern Kansas, USA - Ann L. Allert; Robert J. DiStefano; Christopher J. Schmitt; James F. Fairchild; William G. Brumbaugh (Archives of Environmental Contamination and Toxicology, 2012)

Effects of increasing times of incomplete cerebral ischemia upon the energy state and lipid peroxidation in the rat - R. Vagnozzi; B. Tavazzi; D. Di Pierro; B. Giardina; B. Fraioli; S. Signoretti; S. Distefano; M. Galvano; G. Lazzarino (Experimental Brain Research, 1997)